Drivers of antimicrobial resistance within the communities of Nepal from One Health perspective: a scoping review - Parajuli, Ayuska; Mitchell, Jessica; King, Natalie; Arjyal, Abriti; Latham, Sophia; King, Rebecca; Baral, Sushil (Frontiers in Public Health, 2024)
Background A major driver of antimicrobial resistance (AMR) is the inappropriate use of antimicrobials. At the community level, people are often engaged in behaviors that drive AMR within human, animal, and environmental (One Health) impacts. This scoping review consolidates research to determine (a) the community’s knowledge, attitudes, and practices around AMR; (b) existing community-based interventions; and (c) barriers and enablers to addressing AMR in Nepal. Methods This scoping review follows the Joanna Briggs Institute scoping review methodology. Literature indexed in PubMed, Scopus, CINAHL, Global Index Medicus, HINARI-SUMMON, Embase (Ovid), Global Health (Ovid), CAB Abstracts (Ovid), Web of Science, and Google Scholar between January 2000 and January 2023 were reviewed for inclusion. Articles were included in the review if they considered the issues of AMR at the community level in Nepal; this excluded clinical and laboratory-based studies. A total of 47 studies met these criteria, were extracted, and analyzed to consolidate the key themes. Results A total of 31 (66%) articles exclusively included human health; five (11%) concentrated only on animal health; no studies solely focused on environmental aspects of AMR; and the remaining studies jointly presented human, animal, and environmental aspects. Findings revealed inadequate knowledge accompanied by inappropriate practice in both the human and animal health sectors. Four community interventions improved knowledge and practices on the appropriate use of antimicrobials among community people. However, various social and economic factors were found as barriers to the appropriate use of antimicrobials in the community. Conclusion Community engagement and One Health approaches could be key tools to improve awareness of AMR and promote behavioral change related to AM use in communities, as current studies have revealed inadequate knowledge alongside inappropriate practices shared in both human and animal health sectors. Systematic review registration DOI: 10.17605/OSF.IO/FV326